A Power factor corrector using interleaved boost fuzzy-logic converter: design, analysis, and implementation - Mentari Putri Jati (Journal of Engineering and Applied Technology, 2021)
The technology for developing power factor correction is increasingly being discussed because of the increasing number of nonlinear loads that exist. This is related to power quality which can affect load system performance because nonlinear loads cause low power factor and the appearance of harmonic currents. However, it takes a power factor corrector converter that has a simple construction and reliable performance. Interleaved Boost Converter is often applied as a power factor corrector converter because it has these advantages. Combined with a fuzzy controller it is a proposed system to achieve a near unity power factor. The discontinuous Conduction Mode (DCM) technique is used because it has an efficient inductor design. The results of the proposed system design were proven by simulation and hardware implementation which resulted in significant power factor improvements.